Cancer-Mediated Muscle Cachexia: Etiology and Clinical Management - Siff, Thomas (Trends Endocrinol Metab, 2021)
Muscle cachexia has a major detrimental impact on cancer patients, being responsible for 30% of all cancer deaths. It is characterized by a debilitating loss in muscle mass and function, which ultimately deteriorates patients’ quality of life and dampens therapeutic treatment efficacy. Muscle cachexia stems from widespread alterations in whole-body metabolism as well as immunity and neuroendocrine functions, and these global defects often culminate in aberrant signaling within skeletal muscle, causing muscle protein breakdown and attendant muscle atrophy. This review summarizes recent landmark discoveries that significantly enhance our understanding of the molecular etiology of cancer-driven muscle cachexia, and further discuss emerging therapeutic approaches seeking to simultaneously target those newly-discovered mechanisms to efficiently curb this lethal syndrome.